Islamic Relief as a Transnational Advocacy Network in Building Global Solidarity for Gaza - Nabila, Nura Alanda; Azzah, Zhafirah Fatin; Nuraeni, Nuraeni; Heryadi, R. Dudy (Prodi Hubungan Internasional Program Magister Univ. Muhammadiyah Yogyakarta, 2025)
This article examines the role of Islamic Relief in supporting Palestine from the perspective of the Transnational Advocacy Network. The conflict in Palestine, particularly in Gaza, raises the central question of how non-governmental actors contribute to global advocacy efforts amid the large-scale civilian suffering. The article is based on qualitative research, utilizing a literature review as a data collection technique, with constructivism as the theoretical framework. This study positions Islamic Relief as a transnational humanitarian organization whose work is shaped and rooted in Islamic values. The findings showed that the efforts to address the crisis in Gaza are carried out by Islamic Relief, not only by delivering direct social assistance but also by mobilizing public awareness through their online platforms. By prioritizing narratives of humanity and global justice, Islamic Relief attempts to strengthen the international advocacy network supporting Palestine. From a constructivist perspective, Islamic Relief becomes an actor who shapes global response to the current situation in Gaza that leads to genocide. Thus, this study highlighted Islamic Relief's role in building global solidarity for Palestine, based on an interpretation of core Islamic values that require the organization to go beyond mere aid and actively engage in transnational advocacy.